Meningite Assética Associada à Terapêutica com Imunoglobulina Endovenosa - Francisco, T (2014)
Aseptic meningitis can be an adverse drug reaction to intravenous immunoglobulin. We describe a previously healthy 4-yearold boy, admitted for idiopathic thrombocytopaenic purpura. He received two infusions of intravenous immunoglobulin. Four hours after the last administration the patient developed a meningeal syndrome. Analysis of cerebrospinal fluid revealed 500 cells/μl (predominantly neutrophils) and normal biochemistry. Bacteriological and virological tests were negative. After 48h he was asymptomatic. Given the absence of other aetiological factors and the temporal relationship between the administration of immunoglobulin and the development of symptoms, we believe the patient had an aseptic meningitis related to intravenous immunoglobulin. This therapy may cause headache, fever and vomiting; however, lumbar puncture is not usually performed, so this complication may be underdiagnosed.